Макроэкономика: учебное пособие - Плотницкий М. И. Михаил Иванович; Лобкович Э. И. Эдуард Иванович; Муталимов М. Г. Магомед Гамидович; Примаченок Г. А. (Экономическое образование)
Исключено из фонда НТБ ТПУ